Thunder rolling in the mountains - O'Dell, Scott 1898-1989; Hall, Elizabeth (Dell, 2007)
In the late nineteenth century, a young Nez Percé girl relates how her people were driven off their land by the U.S. Army and forced to retreat north until their eventual surrender. From the viewpoint of Chief Joseph's daughter, this historical novel concerns the forced removal of the Nez Perce from their homeland in 1877. It is spring of 1877 when fourteen-year-old Sound of Running Feet, daughter of Chief Joseph of the Nez Perce, sees white people panning gold in the little creek that feeds the Wallowa River, and brings word of them to her father. "They are the first, but more are on the way," he says. "We are few and they are many. They will devour us." It is Sound of Running Feet who narrates the story of her tribe's fate. Readers will be gripped as she shares with us her respect for her father, her love for handsome Swan Necklace, and her destiny
A Yearling book
Keywords: Nez Percé Indians / Juvenile fiction; Nez Percé Indians / Fiction; Indians of North America / Fiction; Nez Perce Indians / Fiction; Indianer; Jugendbuch